The Analysis of Students' Difficulties In Speaking English at the Tenth Grade of SMK N 2 Purworejo - Catur Widy Asworo (Universitas Bengkulu, 2019)
The aims of the study are mainly to know the students’ difficulties in speaking, and to know the strategy used by teacher to overcome the speaking problems.The participants of the study were 36 students of the tenth grade of SMK N 2 Purworejo.The instruments used in this research were questionnaire, interview and documentation. After getting the data, the writer analyzed them to determine category of students’ speaking skill, students’ speaking difficulties and teacher strategies.The result of the study shows that the mean score of students skill in speaking is 64.8. It belongs to sufficient category. The students’ speaking difficulties covered linguistic and non linguistics problems. The linguistic problems include lack of vocabulary, pronunciation, grammar knowledge, while non linguistic problems, namely inhibition, nothing to say, uneven participant, mother tounge interference,anxiety, shyness, lack of self confident and low motivation. To solve the problems, the teacher has strategies such as drilling, brainstorming, role playing and giving the students motivation.